Short-term results of the pulmonary embolism treatment - A. S. Nikonenko; A. A. Nikonenko; S. A. Matvieiev (Zaporožskij Medicinskij Žurnal)
Aim. Acute pulmonary embolism (PE) is a common and often fatal disease with the level of mortality in the acute phase from 7 to 11%. In order to develop indications to thrombolytic therapy the short-term results of treatment with the use of combination therapy were studied. This treatment included: thrombolysis and /or anticoagulant therapy, with the usage of new oral anticoagulants and treatment of acute pulmonary hypertension. 231 patients with pulmonary embolism were examined.